2015
DOI: 10.1002/alr.21599
|View full text |Cite
|
Sign up to set email alerts
|

Does comorbid obesity impact quality of life outcomes in patients undergoing endoscopic sinus surgery?

Abstract: Background Both obesity and chronic rhinosinusitis (CRS) are characterized by inflammation. Furthermore, both disease processes are independently associated with decreases in quality-of-life (QOL). We sought to investigate the role of comorbid obesity in QOL outcomes in CRS patients undergoing endoscopic sinus surgery (ESS). Methods Adult patients with medically refractory CRS (n=241) were prospectively enrolled into a multi-institutional treatment outcomes investigation. Body mass index (BMI) calculations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…Studies with the same cohort of patients were considered duplicates, leading to 31 excluded studies. 17-47 An additional 78 studies failed to meet inclusion criteria, leading to a final list of 15 distinct patient studies. 48-62…”
Section: Resultsmentioning
confidence: 99%
“…Studies with the same cohort of patients were considered duplicates, leading to 31 excluded studies. 17-47 An additional 78 studies failed to meet inclusion criteria, leading to a final list of 15 distinct patient studies. 48-62…”
Section: Resultsmentioning
confidence: 99%
“…Full‐length texts were then reviewed, and an additional 23 studies identified from references. A total of 31 studies were considered to be duplicates from the same cohort, and an additional 53 failed to meet inclusion/exclusion criteria. The final study list included 40 unique patient cohorts published from 2008 to 2016 and representing institutions from North America (n = 14), Europe (n = 12), Middle East (n = 6), Australia (n = 3), Asia (n = 3), and South America (n = 2) .…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, Kanagalingam et al . and Steele's group demonstrated obesity had no effect on severity of sinonasal disease symptoms in asthmatics or in patients prior to endoscopic sinus surgery 22,23 …”
Section: Discussionmentioning
confidence: 98%
“…21 Conversely, Kanagalingam et al and Steele's group demonstrated obesity had no effect on severity of sinonasal disease symptoms in asthmatics or in patients prior to endoscopic sinus surgery. 22,23 The link between smoking and nasal airway obstruction seemed a little stronger, however. For example, the sequelae of smoking (chronic obstructive airways disease) lead to higher SNOT-22 scores.…”
Section: Discussionmentioning
confidence: 99%